2020
DOI: 10.3345/cep.2019.00381
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotics use for preventing sepsis and necrotizing enterocolitis in very low birth weight neonates: a randomized controlled trial

Abstract: Background: Probiotics and prebiotics have strain-specific effects on the host. Synbiotics, a mixture of probiotics and prebiotics, are proposed to have more beneficial effects on the host than either agent has alone.Purpose: We performed a randomized controlled trial to investigate the effect of Lactobacillus and Bifidobacterium together with oligosaccharides and lactoferrin on the development of necrotizing enterocolitis (NEC) or sepsis in very low birth weight neonates.Methods: Neonates with a gestational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In a relatively small multi-center RCT, enteral administration of carotenoids did not alter NEC incidence (OR 0.34 (95% CI 0.07-1.66) [241]. A mixture of probiotics, prebiotics and lactoferrin did reduce the overall NEC incidence and the incidence of NEC stage ≥2 in a small RCT ((RR 0.16 (95% CI 0.03-0.77) and RR 0.56 (95% CI 0.47-0.67) respectively) [242]. For both interventions, certainty of evidence was scored as low.…”
Section: Other Feeding Interventionsmentioning
confidence: 92%
“…In a relatively small multi-center RCT, enteral administration of carotenoids did not alter NEC incidence (OR 0.34 (95% CI 0.07-1.66) [241]. A mixture of probiotics, prebiotics and lactoferrin did reduce the overall NEC incidence and the incidence of NEC stage ≥2 in a small RCT ((RR 0.16 (95% CI 0.03-0.77) and RR 0.56 (95% CI 0.47-0.67) respectively) [242]. For both interventions, certainty of evidence was scored as low.…”
Section: Other Feeding Interventionsmentioning
confidence: 92%
“…In this analysis, the development of NEC and sepsis was significantly decreased when compared to breast fed controls without synbiotic supplementation [ 76 ]. A prospective, double-blinded RCT was performed in very low birth weight infants ≤32 weeks’ gestation and <1500 g birth weight receiving enteral feeds with a synbiotic combination ( L. rhamnosus , L. plantarum , L. casei , B. lactis plus FOS, and galactooligosaccharide) in addition to lactoferrin and vitamins versus placebo [ 77 ]. This analysis yielded a reduced incidence in all stages of NEC with no difference in the incidence of late-onset culture-positive sepsis [ 77 ].…”
Section: Synbioticsmentioning
confidence: 99%
“…To the best of our knowledge, there has not been any research on the effect of synbiotics on C. sakazakii , although several studies have shown reduced morbidity or mortality of NEC after synbiotic application ( Dilli et al, 2015 ; Sreenivasa et al, 2015 ; Nandhini et al, 2016 ; Pehlevan et al, 2020 ), and other studies have shown the beneficial effects of synbiotics on other foodborne pathogens such as Salmonella enterica , Shigella sonnei , and enteropathogenic and enterohemorrhagic E. coli ( Likotrafiti et al, 2016 ; Kusmivati and Wahyuningsih, 2018 ; Shanmugasundaram et al, 2019 ; Tabashsum et al, 2019 ; Piatek et al, 2020 ). The antimicrobial potential of synbiotics is likely dependent on the pathogen-synbiotic combination as E. coli and Campylobacter jejuni were inhibited by synbiotics when cultured in a multi-batch culture system containing a synbiotic with a pathogen, but in a single continuous culture system only C. jejuni was inhibited ( Fooks and Gibson, 2003 ).…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%